Kajian Sarana Dan Prasarana Terminal Daya Kota Makassar - Charles Kamba; Rais Rachman; Gidion Suretno Panannangan (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Makassar is one of the cities with a dense population level and the movement of people from one city to another. One of the factors that support the occurrence of mobility is the passenger terminal function as a vehicle stopover to raise and lower passengers. One of the terminals located in Makassar City is the Daya Regional Terminal, which is a type A terminal. This research aims to determine the level of service and user satisfaction in the application of facilities and infrastructure at the Daya Regional Terminal. The research method used in this research is primary data collection directly in the field in the form of distributing questionnaire sheets to terminal visitors which will be processed in the Importance and Permormance Analysis (IPA) method. The result of this research is that the facilities at the Daya terminal fulfill the application for terminal visitors, and the overall result of the facilities in the Daya terminal is the level of visitor satisfaction or Customer Satisfaction Index obtained 74.12%, this figure is included in the satisfied category.